PENGARUH DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. MARGAGUNA MAJU BERSAMA JAKARTA SELATAN - Achmad Chaeikal Firdaus; Ali Zaenal Abidin (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of work discipline and motivation work on employee performance at PT Margaguna Maju Bersama South Jakarta, both partially and simultaneously. This research method uses quantitative methods with a sample size of 64 respondents, the data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, coefficient of determination analysis test, t test and f test. Based on the results of the t test, it is obtained that t count is 3.084> 1,999 and the significance value for the Work Discipline variable (X1) is 0.003, the significant value is smaller than the probability value of 0.05 or 0.003 <0.05, meaning that the Work Discipline variable (X1) has a positive and significant effect on the Employee Performance variable (Y). at PT Margaguna Maju Bersama South Jakarta. Based on the results of the t test, the t value is 6,019> 1,999 and the significance value for the Work motivation variable (X2) is 0.000, the significance value is greater than the probability value of 0.05 or 0.000 <0.05, meaning that the Work Motivation variable (X2) has a positive and significant effect on the Employee Performance variable (Y). at PT Margaguna Maju Bersama South Jakarta. Based on the results of the f test, the calculated f value is 16,048 > 3,15 and the significance value is 0.001 <0.05. So it can be concluded that the variables of Work Discipline (X1) and Work Motivation (X2) simultaneously have a positive and significant influence on Employee Performance (Y). at PT Margaguna Maju Bersama South Jakarta.